Ecofriendly synthesis of monodispersed silver nanoparticles using Andean Mortiño berry as reductant and its photocatalytic activity. (February 2019) - Kumar, Brajesh; Vizuete, Karla Sofía; Sharma, Vishal; Debut, Alexis; Cumbal, Luis
Abstract: Mortiño ( Vaccinium floribundum Kunth) berry is an endemic fruit from the Andes region and rich in vitamins, polyphenolic and anthocyanin compounds. The present report describes the Mortiño berry extract mediated biosynthesis of silver nanoparticles and their photocatalytic evaluations. The conditions for the synthesis of silver nanoparticles were optimised by adjusting the amount of berry extract, pH, and time. Biosynthesis of silver nanoparticles was primarily identified by the appearance of yellow colour and confirmed by measurements of UV–visible spectroscopy. Particle size distribution, morphology and crystalline nature of silver nanoparticles were characterised by transmission electron microscopy, dynamic light scattering, and X-ray diffraction techniques. All characterisation technique reveals that the generated silver nanoparticles were stable, non-aggregated, monodispersed, spherical shape with an average size of 20.5 ± 1.5 nm and face centered cubic in nature. In order to evaluate photocatalytic activity, degradation of methylene blue dye by silver nanoparticles under sunlight was used as model system. It showed photocatalytic activity against methylene blue dye (5 mg/L, k = 0.00707788 min −1 ), efficiently. This ecofriendly approach highlighted the importance of Mortiño berry in green nanotechnology and generates a new scope of other Andean fruits in engineering applications. Graphical abstract: Highlights: First report on Mortiño berry extract for the synthesis of monodispersed silver nanoparticles. TEM-DLS analysis confirmed the average nanoparticles size is 20.5 ± 1.5 nm. Silver nanoparticles showed photocatalytic activity for the degradation of methylene blue dye. Environmentally benign and low-cost method is suggested.